Chemical composition and antimicrobial properties of different basil essential oils chemotypes from Togo - Koffi Koba; P.W. Poutouli; Christine Raynaud; Jean-Pierre Chaumont; Komla Sanda (Bangladesh Pharmacological Society, 2009)
The aerial parts essential oils of Ocimum basilicum (Lamiaceae) from Togo were steam-distilled and investigated for their percentage composition (GC and GC/MS) and in vitro antimicrobial activities. Five oil chemotypes were identified and classified as follows in line with their principal components: estragole type; linalool/estragole type; methyleugenol type; methyleugenol/t-anethole type; t-anethole type. The in vitro microbiological experiments revealed that only the methyleugenol and methyleugenol/t-anethole chemotypes were active against tested fungi and bacteria. Their minimum inhibitory concentrations (MIC) ranged from 80 to 150 µl.l-1 and from 200 to 500 µl.l-1 respectively. Likewise, on tested bacteria the MIC varied from 200 µl.l-1 to 400 µl.l-1 and from 250 to 500 µl.l-1 respectively. These findings are supportive of the potential of both basil oil chemotypes for use as active ingredients in natural antibiotic drugs.